2009
DOI: 10.1002/adsc.200900074
|View full text |Cite
|
Sign up to set email alerts
|

Micellar Effects in Olefin Hydroformylation Catalysed by Neutral, Calix[4]arene‐Diphosphite Rhodium Complexes

Abstract: Abstract:The combination of calixarene-derived surfactants and neutral rhodium complexes containing a hemispherical "1,3-calix-diphosphite" ligand led to efficient catalysts for the hydroformylation of octene and other olefins in water. While the surfactants allowed the formation of micelles that dissolve both the catalyst and the alkene, thereby resulting in high olefin:rhodium ratios, the diphosphite provided a tight envelope about the catalytic centre able to drive the reaction towards the linear aldehydes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 32 publications
(47 reference statements)
0
33
0
Order By: Relevance
“…[26] Thus, with a carbon CO/H 2 ratio of 1:2 instead of 1:1 the conversion rose from 75.4-88.7 for 1-octene and from 64.1-91.9 % for styrene, without altering significantly the regioselectivities (Table 1, Taking into account the above results, the hydroformylation tests presented hereafter were all performed using a CO:H 2 ratio of 1:2. For the hydroformylation of 1-octene, 1-hexene, allyl benzyl ether, and 2-vinylnaphthalene 9 equiv.…”
Section: Entrymentioning
confidence: 96%
See 1 more Smart Citation
“…[26] Thus, with a carbon CO/H 2 ratio of 1:2 instead of 1:1 the conversion rose from 75.4-88.7 for 1-octene and from 64.1-91.9 % for styrene, without altering significantly the regioselectivities (Table 1, Taking into account the above results, the hydroformylation tests presented hereafter were all performed using a CO:H 2 ratio of 1:2. For the hydroformylation of 1-octene, 1-hexene, allyl benzyl ether, and 2-vinylnaphthalene 9 equiv.…”
Section: Entrymentioning
confidence: 96%
“…[24,25] Recently, we showed that these neutral complexes may also be used in aqueous medium, provided a sulfonated calix [4]arene acting as surfactant is added to the reaction mixture. [26] No significant loss of regioselectivity was observed. Under these conditions, micelles formed, the catalytic process taking place in concentrated microenvironments characterised by a high metal-to-olefin ratio, which incidentally increases the rate of the reaction.…”
Section: Introductionmentioning
confidence: 96%
“…Ligands 2 and 4 and complexes 6 and 7 were obtained according to previously reported synthetic procedures. [18,19] HP NMR spectroscopic measurements were carried out by using a Bruker Avance II 200 spectrometer operating at 200. and a titanium high-pressure charging head (ICCOM-CNR, Sesto-Fiorentino, Italy) were used. [40] HP-IR experiments were performed in a highpressure IR cell (ICCOM-CNR) consisting of a 75 mL autoclave equipped with ZnS windows (4 mm thickness, 8 mm diameter, optical path length 0.2 mm).…”
Section: Methodsmentioning
confidence: 99%
“…In the solid state, the calix [4]arene cavity adopts a typical pinched cone conformation [1][2][3], with interplanar angles between opposite phenoxy rings of 21.2°and 76.2°, respectively. The separations between the aromatic para-carbon atoms of opposite phenolic rings are 4.26 and 9.97 Å, respectively.…”
Section: Discussionmentioning
confidence: 99%